Micro-Angiographic Studies of End-to End Anastomosis of Femoral Artery in Rats* - F.M. Tripathi; A.K. Chaudhury; D.K. Rai (Indian Journal of Plastic Surgery)
Fifteen albino rats each weighing 300 to 400 gms were selected for micro angiographic studies. Microsurgical end-to-end femoral vein anastomosis was carried out and cream-o-bar 50% aqueous suspension was injected with the help of a D.K. Injector. A patency rate of 73% was achieved in the six week follow up study. Results of angiographic changes observed in the vascular lumen following anastomosis have been analysed and are being presented.